Boron-modified cobalt iron layered double hydroxides for high efficiency seawater oxidation. (May 2021) - Wu, Libo; Yu, Luo; Zhu, Qiancheng; McElhenny, Brian; Zhang, Fanghao; Wu, Chunzheng; Xing, Xinxin; Bao, Jiming; Chen, Shuo; Ren, Zhifeng
Abstract: Developing efficient and stable oxygen evolution reaction (OER) catalysts that can work well at high current densities for seawater electrolysis is desirable but remains a significant challenge. Here a novel and scalable strategy is developed to synthesize partially amorphous boron-modified cobalt iron layered double hydroxides (B-Co2 Fe LDH). Benefiting from enhanced electronic kinetics and abundant active sites, this hierarchical nanosheet-nanoflake-structured B-Co2 Fe LDH catalyst shows superb OER catalytic activity, requiring overpotentials of 205 and 246 mV to drive current densities of 10 and 100 mA cm −2, respectively, in 1 M KOH, along with a small Tafel slope of 39.2 mV dec −1 . Its partial amorphousness feature leads to enhanced stability and corrosion resistance, which help the B-Co2 Fe LDH catalyst to work well in the critical seawater condition. It requires overpotentials of 310 and 376 mV to drive current densities of 100 and 500 mA cm −2, respectively, in 1 M KOH seawater and can work continuously for 100 h without producing any hypochlorite. This work can enable the development of LDH catalysts for highly selective seawater oxidation using a general approach. Graphical Abstract: ga1 Highlights: A novel strategy is developed to synthesize partially amorphous boron-modified cobalt iron layered double hydroxides. The B-Co2 Fe LDH catalyst has a hierarchical nanosheet-nanoflake structure to expose active sites with strong corrosion resistance. It requires low overpotential and shows excellent stability for OER in alkaline seawater. In situ Raman and post-OER analysis are applied to analyze the transformation of B-Co2 Fe LDH during OER.